Update on Immunology of COVID-19 Disease and Potential Strategy for Controlling - Dezfuli, Neda K. (Tanaffos, 2020)
Coronavirus disease 2019 (COVID-19) is caused by a novel form of the coronavirus that caused severe acute respiratory syndrome (SARS). SARS-CoV-2 raised in China and has broadcast to 261 countries globally. SARS-CoV-2 a member of β-coronavirus family and has an almost matching genome sequence to a bat coronavirus, pointing to the bat as the natural host before it was transmitted to humans. SARS-CoV-2 uses the same receptor, angiotensin-converting enzyme 2 (ACE2) as that used by SARS-CoV and principally infects the respiratory tract. The clinical symptoms of COVID-19 patients include fever, cough and fatigue whilst small populations of patients have gastrointestinal symptoms. The old people and people with underlying metabolic and cardiovascular diseases are more affected to infection and have worse outcomes. These may be associated with acute respiratory distress syndrome (ARDS) and a cytokine storm. In this review, we discuss the pathogenesis and clinical characteristics of disease and the pharmacologic approaches that may control COVID-19.